Blue carbon in sediment from Sanggou Bay: composition, burial flux and its response to human activities - Yang, Shu; Yang, Qian; Song, Xianli; Zhou, Wei; Liu, Jihua; Qi, Xiandong; Chen, Junfeng; Huang, Jun; Li, Bin; Sun, Yao (Frontiers in Marine Science, 2024)
Marine primary production and terrestrial input are the main sources of buried carbon in sediments of marginal seas. Only marine-source carbon buried in sediments, fixed and stored by marine ecosystems, belongs to “blue carbon” and reflects marine ecosystems’ carbon sink function. The pattern of buried blue carbon in sediments, its flux, and its relationship with environmental changes remain unclear. The study aimed to investigate the composition of blue carbon in the sediments of Sanggou Bay, a special type of marginal sea. The analysis of sediment carbon sources was conducted through the C/N ratio and microscopic examination. The study also examined the long-term changes in the blue carbon burial fluxes. Results showed Blue carbon, which is sea-sourced carbon, accounted for about 23% of the total carbon content and its concentration ranged from 0.17% to 0.51%, with an average of about 0.25% ± 0.10%. The content of organic blue carbon in this sea area ranges from 0.09% to 0.26%, with an average of around 0.18% ± 0.04%. It constitutes approximately 72% of the buried blue carbon in the sediment, making it the primary component of buried blue carbon. Meanwhile, the content of inorganic blue carbon ranges from 0.01% to 0.32%. Over the past 70 years, the burial fluxes of sedimentary blue carbon, organic blue carbon and inorganic blue carbon in the Sanggou Bay are about 0.54 ± 0.22 mmol/(cm2a), 0.38 ± 0.07 mmol/(cm2a) and 0.17 ± 0.22 mmol/(cm2a), respectively; their long-term changes have been significantly affected by human aquaculture activities. Large-scale raft-rack aquaculture activities have caused a reduction in water flow velocity and an increase in the deposition of particulate organic matter, which in turn has led to the burial of organic blue carbon in the sediment. Additionally, the competition between aquaculture products and small calcareous organisms, such as mussels, foraminifera, may have inhibited the growth of small calcareous organisms. We suggest this has resulted in reduced burial fluxes of inorganic blue carbon and a decrease in its proportion among total blue carbon in the sea area. Our findings imply that aquaculture activities in Sanggou Bay had a negative impact on the burial of blue carbon in the sediments.